Hubungan antara Derajat Hipertensi dan Elongasi Aorta pada Pemeriksaan Foto Toraks - Firstyani, Maria Leony Rahajeng (Jurnal Kedokteran Indonesia, 2011)
Background: Despite it is general thought that the aorta lengthens with hypertension, its empiricalevidence from Indonesian population is lacking. This study aimed to examine the relationship betweengrade of hypertension and aortic elongation on the chest X-ray examination.Methods: A cross-sectional study has been carried out at the Radiology Department, Dr. MoewardiHospital, from May 23rd to June 23rd 2011. A sample of 60 subjects aged from 20 to 80 years old wereselected by purposive sampling. Postero-anterior chest X-ray photograph including six pairs of anteriorribs and ten pairs of posterior ribs was taken with sufficient inspiration. Subjects with other abnormalcardiac and aortic valve were excluded. Study subjects filled-in informed consent form and weremeasured for aortic elongation, i.e. the length between the top of aortic arch and incisura jugularissterni. The blood pressure was checked. The researcher also searched the subjectsâ medical record forsecondary data. Odds Ratio (OR) was used to measure the strength of association, and chi-square totest its statistical significance, on SPSS 17.0 for Windows.Results: Individuals with prehypertension had 5 times higher risk of aortic elongation than normalindividuals (OR= 5.09; 95%CI 1.14 to 22.62; p=0.013). Individuals with grade 1 hypertension had 8 timeshigher risk of aortic elongation than normal individuals (OR= 8.00; 95%CI 1.39 to 45.75; p=0.007).Individuals with grade 2 hypertension had 61 times higher risk of aortic elongation than normalindividuals (OR=60.71; 95%CI 2.76 to 1332; p<0.001).Conclusion: There is a strong and statistically significant âdose-response relationshipâ between gradeof hypertension and aortic elongation. Aortic elongation can be used as a sensitive and reliable markerfor diagnosing pre-hypertension and hypertension..Keyword: grade of hypertension, aortic elongation